Factors influencing student migration to Bangladesh: Mediating effect of host country support and moderating effect of geographical location and gender - Abdulhakim Usman; Mahbub Hasan; Mohammad Nurul Alam (Social Sciences and Humanities Open)
This study aimed to investigate the motivations of international students selecting Bangladesh for higher education, utilizing twenty hypotheses incorporating social, economic, and political aspects alongside the push-pull theory. Analyzing data from 187 tertiary-level international students through a quantitative survey and partial least squares structural equation modeling (PLS-SEM), the study found direct associations of Scholarship Opportunity (SO) and Living Cost (LC) with students' migration (SM) in Bangladesh. However, Job Opportunity (JO), culture (CUL), and War & Persecution (W&P) did not significantly affect SM. Host country support (HCS) played a significant mediating role in relationships involving JO, CUL, SO, and LC, but not in the relationship with W&P. This research expands migration theories beyond the conventional ‘push-pull’ paradigm, providing a comprehensive understanding of international students' motivations in Bangladesh. It identifies SO and LC as direct influencers, while emphasizing the substantial mediating role of HCS, contributing to nuanced insights into decision-making processes. To attract a diverse pool of international students, institutions in Bangladesh are recommended to strategically enhance the visibility of scholarship programs. Additionally, recognizing the non-significant impact of JO on student migration, host institutions have an opportunity to improve job prospects through targeted support programs or industry partnerships. However, the study's limitations include its single-context focus on international students in Bangladesh, potentially limiting generalizability. Future research should replicate the study in diverse settings for broader applicability. Also, further research could involve cross-cultural comparative studies for a comprehensive understanding and a longitudinal approach to track evolving motivations over students' educational journeys.